Відповідь:
1)
2) V=a*b*h
3)
4) 2a(x-y)+4b(x-y)=(2a+4b)*(x-y)
2.5x-2.5y+az-bz=2.5(x-y)+z(a-b)
5) S=a*b-(c*d)
Пояснення:
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь:
1)![14x^{3+2}y^{2} z^{4+2}d^{8} =14x^{5}y^{2} z^{6}d^{8} 14x^{3+2}y^{2} z^{4+2}d^{8} =14x^{5}y^{2} z^{6}d^{8}](https://tex.z-dn.net/?f=14x%5E%7B3%2B2%7Dy%5E%7B2%7D%20%20z%5E%7B4%2B2%7Dd%5E%7B8%7D%20%20%3D14x%5E%7B5%7Dy%5E%7B2%7D%20%20z%5E%7B6%7Dd%5E%7B8%7D)
2) V=a*b*h
3)![2x^{2} -2x+6+5x^{2} +7x-7=7x^{2} +5x-1 2x^{2} -2x+6+5x^{2} +7x-7=7x^{2} +5x-1](https://tex.z-dn.net/?f=2x%5E%7B2%7D%20-2x%2B6%2B5x%5E%7B2%7D%20%2B7x-7%3D7x%5E%7B2%7D%20%2B5x-1)
4) 2a(x-y)+4b(x-y)=(2a+4b)*(x-y)
2.5x-2.5y+az-bz=2.5(x-y)+z(a-b)
5) S=a*b-(c*d)
Пояснення: